Lipid Profile Status In Surgical Menopause - Kabir, Farhana; Jahan, Nasim; Sultana, Nayma; Akter, Rezina (Journal of Bangladesh Society of Physiologist, 2012)
Background: Dyslipidaemia in both surgical and natural menopausal women is a common health hazard all over the world. Moreover, the surgical menopausal women may have greater chance of this disorder than those of natural menopausal women. Objective: To observe lipid profile level in surgical menopausal women in Bangladesh. Methods: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka from 1st January 2010 to 31st December 2010. A total number of 90 female subjects were included in this study. They were divided into control and study groups. Among them 6o women were taken as control (30 premenopausal women- group A and 30 natural menopausal women -group B) and 30 were taken as study (surgical menopausal-group C).However, age range of premanopausal women were from 30-35 years, natural menopausal women from 50-60 years and surgical menopausal women from 45-55 years. All the menopausal women were selected from Out Patient Department (OPD) of Gynaecology and Obstetrics of Sir Salimullah Medical College and Mitford Hospital. Premenopausal women were selected by personal contact. Serum lipid profile and serum estrogen levels of all participants were estimated by enzymatic method and by AxSYM method respectively. The statistical analysis was done by using appropriate method as applicable. Results: In this study, mean serum triglyceride (TG) level was significantly (p<0.05) higher and serum high density lipoprotein cholesterol (HDL-C) level was significantly (p<0.001) lower in surgical menopausal women than those of natural menopausal women. . Again, mean serum estrogen level was significantly (p<0.001) lower in surgical menopausal women than that of natural menopausal women. Conclusion: The present study revealed that surgical menopausal women have greater chance of dyslipidaemia than those of natural menopausal women. DOI: http://dx.doi.org/10.3329/jbsp.v6i2.9763 JBSP 2011 6(2): 127-133